2010
DOI: 10.2134/jeq2009.0504
|View full text |Cite
|
Sign up to set email alerts
|

Estimating Dissolved Reactive Phosphorus Concentration in Surface Runoff Water from Major Ontario Soils

Abstract: Phosphorus (P) loss from agricultural land in surface runoff can contribute to eutrophication of surface water. This study was conducted to evaluate a range of environmental and agronomic soil P tests as indicators of potential soil surface runoff dissolved reactive P (DRP) losses from Ontario soils. The soil samples (0- to 20-cm depth) were collected from six soil series in Ontario, with 10 sites each to provide a wide range of soil test P (STP) values. Rainfall simulation studies were conducted following the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
54
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 59 publications
(59 citation statements)
references
References 42 publications
4
54
0
Order By: Relevance
“…Moreover, several studies have shown high correlation between dissolved reactive P in runoff and WEP (Pote et al, 1996;Sharpley et al, 2001;Davis et al, 2005). According to Wang et al (2009), these relationships are soil-specific and vary with soil type, soil clay content, slope, and soil management. Because it is impractical to implement a specific environmental soil test P for each soil type, several efforts have been made to find an agri-environmental soil test that can be applied to the major soils of a given region, considering some soil properties (Ige et al, 2005).…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…Moreover, several studies have shown high correlation between dissolved reactive P in runoff and WEP (Pote et al, 1996;Sharpley et al, 2001;Davis et al, 2005). According to Wang et al (2009), these relationships are soil-specific and vary with soil type, soil clay content, slope, and soil management. Because it is impractical to implement a specific environmental soil test P for each soil type, several efforts have been made to find an agri-environmental soil test that can be applied to the major soils of a given region, considering some soil properties (Ige et al, 2005).…”
Section: Resultsmentioning
confidence: 99%
“…Because it is impractical to implement a specific environmental soil test P for each soil type, several efforts have been made to find an agri-environmental soil test that can be applied to the major soils of a given region, considering some soil properties (Ige et al, 2005). Wang et al (2009) Pesq. agropec.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations